Individual and Family Correlates of Calcium-Rich Food Intake among Parents of Early Adolescent Children - Reicks, M.; Ballejos, M.; Goodell, L.; Gunther, C.; Richards, R.; Wong, S.; Auld, G.; Boushey, Carol; Bruhn, C.; Cluskey, M.; Misner, S.; Olson, B.; et al. (Elsevier Inc, 2011)
Background: Most adults do not meet calcium intake recommendations. Little is known about how individual and family factors, including parenting practices that influence early adolescents' intake of calcium-rich foods, affect calcium intake of parents. This information could inform the development of effective nutrition education programs. Objective: To identify individual and family factors associated with intake of calcium-rich foods among parents of early adolescents (aged 10 to 13 years). Design: A cross-sectional survey was used with 14 scales to assess attitudes/preferences and parenting practices regarding calcium-rich foods and a calcium-specific food frequency questionnaire (2006-2007). Participants/setting: A convenience sample of self-reporting non-Hispanic white, Hispanic, and Asian (n=661) parents was recruited in nine states. Parents were the primary meal planner/preparer and completed questionnaires in homes or community settings. Main outcome measures: Predictors of calcium intake from three food groupings-all food sources, dairy foods, and milk. Statistical analyses performed: Multivariate regression analyses identified demographic, attitude/preference, and behavioral factors associated with calcium intake. Results: Most respondents were women (~90%) and 38% had a college degree. Education was positively associated with calcium intake from all three food groupings, whereas having an Asian spouse compared to a non-Hispanic white spouse was negatively associated with calcium intake only from all food sources and from dairy foods. Expectations for and encouragement of healthy beverage intake for early adolescents were positively associated with calcium intake from dairy foods and milk, respectively. Parental concern regarding adequacy of intake was negatively associated, whereas perception of health benefits from calcium-rich foods was positively associated with calcium intake from all food sources and from dairy foods. Between 20% and 32% of the variance in calcium intake from all food groupings was explained in these models. Conclusions: Individual factors and positive parenting practices may be important considerations for nutrition education programs targeted to parents. © 2011 American Dietetic Association.